Diagnosis dan Farmakoterapi Penyakit Paru Obstruktif Kronis: Tinjauan Pustaka - Lukito, Johan Indra (PT Kalbe Farma Tbk., 2025)
Chronic obstructive pulmonary disease (COPD) is a lung disease with chronic respiratory symptoms and exacerbations that can be prevented and treated. COPD is characterized by airfow obstruction that is not fully reversible, generally due to long-term exposure to cigarette smoke, pollution, or other environmental risk factors. Multiaspect COPD assessment after confrmation of COPD diagnosis is needed to guide treatment. The diagnosis is established by spirometry and clinical evaluation, including assessment of symptoms, history of exacerbations, blood eosinophil levels, and the presence of comorbidities. COPD pharmacotherapy aims to reduce symptoms, reduce the risk of exacerbations, and improve the patient’s quality of life. Pharmacotherapy is administered during stable conditions or during exacerbations using bronchodilators alone or in combination, corticosteroids, and other supportive medications according to the patient’s needs, abilities, and condition. Personalized therapy based on symptom severity, history of exacerbations, and patient response. Regular monitoring, proper inhaler technique, and treatment adherence are essential for achieving optimal clinical outcomes.